Giant Intrathoracic Goiter of Atypical Presentation: A Case Report - María B. Iriarte; Eliana I. Morales; Mauricio Velásquez; Valeria Zúñiga; Luz F. Sua; Liliana Fernández-Trujillo (SAGE Publishing, 2020)
Background: The term goiter is used to describe any abnormal growth of the thyroid gland, which can be diffuse or nodular, and can be associated with normal, diminished, or increased thyroid function. Multinodular goiter is a common disease whose prevalence increases at age 50. Clinical manifestations can be due to thyroid function impairment or related to size and location of the gland with compressive symptoms. Intrathoracic location is less frequent, can be mistaken with pulmonary lesions and usually implies a difficult surgical approach. Case presentation: A 66-year-old woman with a history of subtotal thyroidectomy presented with 7-month dyspnea, dry cough. There was no evidence of neck masses, or jugular engorgement. Physical examination was normal. Chest x-ray showed an 11 cm mass in the upper right hemithorax. Computed tomography (CT)-scan, showed calcifications, and compression of the superior vena cava without infiltration, the right subclavian vein and left displacement of the trachea. Distinction between intrapulmonary or mediastinal location was not clear. Biopsy showed thyroid origin, and bilateral thoracotomy was performed with confirmation of a giant multinodular goiter. Conclusions: Intrathoracic goiter should undergo surgical or ablative management if compressive symptoms of the airway and cervical or thoracic vessels are present. The large size of the tumor along with the presentation after thyroidectomy and the seeming location in the right upper lobe made this particular case striking. Specially in the elderly, multidisciplinary perioperative management is key for a successful recovery.